2020
DOI: 10.3390/cells9102246
|View full text |Cite
|
Sign up to set email alerts
|

Protein O-GlcNAcylation Promotes Trophoblast Differentiation at Implantation

Abstract: Embryo implantation begins with blastocyst trophectoderm (TE) attachment to the endometrial epithelium, followed by the breaching of this barrier by TE-derived trophoblast. Dynamic protein modification with O-linked β-N-acetylglucosamine (O-GlcNAcylation) is mediated by O-GlcNAc transferase and O-GlcNAcase (OGA), and couples cellular metabolism to stress adaptation. O-GlcNAcylation is essential for blastocyst formation, but whether there is a role for this system at implantation remains unexplored. Here, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…These pathways would be involved in the O-glycosylation of YAP1, allowing nuclear translocation of YAP1, directly interfering in the first cell differentiation process and playing a decisive role in the specification of the trophectoderm (Chi et al, 2020). More specifically, pharmacological modulation of the O-GlcNAcylation process in pre-implantation stages proved to be important for future differentiation of trophoblast cells, interfering with the expression of transcription factors such as CDX2 and GATA3 (Ruane et al, 2020).…”
Section: First Cell Differentiation Eventmentioning
confidence: 99%
“…These pathways would be involved in the O-glycosylation of YAP1, allowing nuclear translocation of YAP1, directly interfering in the first cell differentiation process and playing a decisive role in the specification of the trophectoderm (Chi et al, 2020). More specifically, pharmacological modulation of the O-GlcNAcylation process in pre-implantation stages proved to be important for future differentiation of trophoblast cells, interfering with the expression of transcription factors such as CDX2 and GATA3 (Ruane et al, 2020).…”
Section: First Cell Differentiation Eventmentioning
confidence: 99%
“…Studies have shown that OSMI-1 can promote tumor cell apoptosis and has certain prospects for cancer treatment [ 39 , 40 ]. It has been shown to be negatively regulated in osteoclasts [ 41 ] and positively regulated during embryonic differentiation [ 42 ] and in corneal epithelial cells [ 43 ]. In this study, using in vitro experiments, we proved that the application of OSMI-1 to inhibit the function of OGT can improve the degree of damage to lung epithelial cells caused by hyperoxia, enhance cell metabolism and proliferation, decrease apoptosis, and promote cell cycle rates.…”
Section: Discussionmentioning
confidence: 99%
“…Protein O -GlcNAcylation has been implicated in embryonic development once the OGT enzyme was determined to be essential for embryonic stem cell viability and OGT depletion was related to embryonic lethality ( 29 , 30 ). Lately, O -GlcNAc was found to promote trophectoderm differentiation into invasive trophoblast, a pattern required during embryo implantation ( 31 ). These data could relate to our findings once SHR presented an increased number of pre-implantation losses along with reduced placental O -GlcNAc expression since 14 DOP.…”
Section: Discussionmentioning
confidence: 99%